Nelfinavir and Lamivudine pharmacokinetics during the first two weeks of life - Mirochnick, Mark (2011)
NICHD HPTN 040/PACTG 1043 Protocol team - We thank the patients and their families who enrolled in this trial. In addition to the authors, members of the NICHD/HPTN 040/PACTG 1043 protocol team include: Belo Horizonte- Federal University of Minas Gerais: Flavia Faleiro Ferreira, Fabiana Kakehasi. Hospital Geral de Nova Iguaçu: Jorge Eurico Ribeiro. Oswaldo Cruz Foundation, Rio de Janeiro (FIOCRUZ): Francisco Inacio Bastos, Beatriz Grinsztejn, Ronaldo Ismerio, Mariza Morgado, Marilia Santini de Oliveira, Valéria Ribeiro. Westat, Inc.: Emmanuel Aluko, Jim Bethel, Yolanda Bertucci, Patty Chen, Barbara Driver, Ruby Duston, Adriana Ferreira, Priya Guyadeen, Sarah Howell, Marsha Johnson, Naomi Leshabane, Lilya Meyerson, Rita Patel, Georgine Price, Susan Raitt, Eunice Yu. NICHD: Jennifer Read, George Siberry. Other protocol team members included Ruth Dickover from the University of CA-Davis, and Elizabeth Smith and Sheryl Zwerski from the National Institute of Allergy and Infectious Diseases, Diane Holland from the University of CA-San Diego Pediatric Pharmacology Laboratory. Pharmaceutical support and representatives included Marita McDonough from Boehringer-Ingelheim Pharmaceuticals, Inc. and Helen Watson from GlaxoSmithKline. This study was supported by NICHD Contract # HHSN267200800001C (NICHD Control # N01-HD-8-0001).